The social animal the hidden sources of love, character, and achievement - Brooks, David 1961- (New York Random House, 2011)
From the influential and hugely popular "New York Times" columnist and bestselling author of "Bobos in Paradise" comes a landmark exploration of how human beings and communities succeed
Award-winning business reporter Charles Duhigg takes us to the thrilling edge of scientific discoveries that explain why habits exist and how they can be changed. With penetrating intelligence and an ability to distill vast amounts of information into engrossing narratives, Duhigg brings to life a whole new understanding of human nature and its potential for transformation
Decision-making -- The map meld -- Mindsight -- Map-making -- Attachment -- Learning -- Norms -- Self-control -- Culture -- Intelligence -- Choice architecture -- Freedom and commitment -- Limerence -- The grand narrative -- Metis -- The insurgency -- Getting older -- Morality -- The leader -- The soft side -- The other education -- Meaning
Includes bibliographical references (pages [381]-406) and index
Keywords: Man-woman relationships|zUnited States; Social mobility|zUnited States; Social status|zUnited States; Elite (Social sciences)|zUnited States; Character; Electronic books